Footpaths and Routes of Eira, Municipality of Oichalia, Messenia, Peloponnese - Αλεξάνδρου, Μαργαρίτα (Πανεπιστήμιο Πελοποννήσου, 2017)
This study investigates the most significant footpaths and routes of Eira in north Messenia, Greece. The mapping of the area was conducted via field research and using GIS, focusing on the footpaths that connect the settlements with the local cultural and natural heritage.The most notable sites are the Temple of Apollo Epikourios, the citadel of Eira and Neda river, as well as its’ springs and waterfalls. Combined with the traditional settlements and the natural environment, Eira has the capacity to attract a plethora of visitors. Alternative tourism and sustainability is the key to the economic, social and environmental development of the area, supported by national grants and local communities’ initiative. Suitable interventions related to the upgrading of the footpath network and the provision of basic tourism services can generate additional local income and transform the area into a popular tourist destination.
Keywords: Γεωγραφική αντίληψη – Ελλάδα – Πελοπόννησος; Πελοπόννησος (Ελλάδα) – Περιγραφή και ταξίδια; Πελοπόννησος (Ελλάδα) -- Αρχαιότητες; Πελοπόννησος; Διαδρομές; Αρχαιότητες